Closing up Shop: Exploring Media Coverage of Plant Closures in Ontario, Canada - Arku, Robert; Sutton, Jesse (Canadian Journal of Regional Science / Revue canadienne des sciences régionales)

(untitled) (Canadian Regional Science Association / Association canadienne des sciences régionales, 2024)
The ongoing issue of plant closures is a significant concern for advanced economies. Consequently, there is a need to update our understanding of plant closures to align with present-day socioeconomic contexts. This paper examines the causes and impacts of plant closures across various contexts in Ontario, Canada, using a media analysis approach. Specifically, 1,157 news articles from 2000 to 2019 are analyzed to gain insights into plant closures in the province. Utilizing media coverage as a novel and robust data source, this study offers a regional perspective on the causes and impacts of plant closures. The identified causes of plant closures include market forces, corporate factors, endogenous factors, economic crises, and globalization. These causes have effects at multiple levels, ranging from the individual to regional.